Diagnostic accuracy of hysterosalpingography compared with hysteroscopy and laparoscopy for female infertility - Aphinives, Chalida; Siriwirot, Siriluksana; Thammaroj, Punthip; Salang, Lingling (Srinagarind Medical Journal, 2022)
Background and Objective: The main anatomical cause of female infertility is congenital or acquired abnormalities. Hysterosalpingography (HSG) is a non-invasive procedure commonly used for the initial evaluation of the fallopian tubes and uterine cavity, especially for female infertility. This study aimed to evaluate the diagnostic accuracy of HSG in infertile women by comparing the findings of intrauterine abnormality with hysteroscopy and patency of fallopian tubes with diagnostic laparoscopy. Methods: A retrospective study from January 2018 to December 2020, among 515 women who underwent HSG, 26 patients had performed hysteroscopy and 19 patients had undergone laparoscopy for infertility. Results: The sensitivity and specificity of HSG to detect abnormal tubal patency were 89% and 70%, hydrosalpinx were 100% and 70%, intrauterine abnormality were 74% and 43%. However, the diagnostic accuracy of HSG to detect cervical abnormality was rather poor with the sensitivity of 0%. Conclusion: In addition to HSG, laparoscopy, hysteroscopy, should be performed for every female infertility case.